Mineral Composition, Antioxidant Properties, Phytochemical and Anti-nutrient Composition of African Palmyra Palm (Borassus aethiopum) Fruit Flour - Abe-Inge, Vincent; Arthur, Christine; Agbenorhevi, Jacob K.; Kpodo, Fidelis M. (American Journal of Food and Nutrition, 2024)
This is an article published by Vincent Abe-Inge, Christine Arthur, Jacob K. Agbenorhevi, and Fidelis M. Kpodo, “Mineral Composition, Antioxidant Properties, Phytochemical and Anti-nutrient Composition of African Palmyra Palm (Borassus aethiopum) Fruit Flour.” American Journal of Food and Nutrition, vol. 6, no. 5 (2018): 143-152.. DOI:10.12691/ajfn-6-5-2 Available online at http://pubs.sciepub.com/ajfn/6/5/2;